Device-Training for Individuals with Thoracic and Lumbar Spinal Cord Injury Using a Powered Exoskeleton for Technically Assisted Mobility: Achievements and User Satisfaction. (17th August 2016) - Platz, Thomas; Gillner, Annett; Borgwaldt, Nicole; Kroll, Sylvia; Roschka, Sybille
Abstract : Objective . Results of a device-training for nonambulatory individuals with thoracic and lumbar spinal cord injury (SCI) using a powered exoskeleton for technically assisted mobility with regard to the achieved level of control of the system after training, user satisfaction, and effects on quality of life (QoL). Methods . Observational single centre study with a 4-week to 5-week intensive inpatient device-training using a powered exoskeleton (ReWalk ™ ). Results . All 7 individuals with SCI who commenced the device-training completed the course of training and achieved basic competences to use the system, that is, the ability to stand up, sit down, keep balance while standing, and walk indoors, at least with a close contact guard. User satisfaction with the system and device-training was documented for several aspects. The quality of life evaluation (SF-12v2 ™ ) indicated that the use of the powered exoskeleton can have positive effects on the perception of individuals with SCI regarding what they can achieve physically. Few adverse events were observed: minor skin lesions and irritations were observed; no falls occurred. Conclusions . The device-training for individuals with thoracic and lumbar SCI was effective and safe. All trained individuals achieved technically assisted mobility with the exoskeleton while still needing a close contact guard.